An investigation of a treatment program for feeding difficulties - Levent, Handan. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Sciences, 1983., 1983)
The purpose of this study is to test the effectiveness of a treatment program to improve the eating habits of children who display problems such as food-refusal, demanding help and/or entertainment in eating, dawdling. and finickeness. The program mainly' involves behavior modification techniques. with supportive measures based on psychoanalytic assumptions. The events which served to maintain inappropriate eating behaviors were withdrawn, while new events to strengthen the desired behavior patterns were introduced. These events mainly involved .the mother's behavior durir.g and after the meals, the amount and timing of the meals, and a reward system made contingent upon appropriate eating behaviors. There were ten children in the· study, between the ages 4 - 2 and 5 - 11. The. treatment program was applied to one group of five children and withheld from the control group of five. It was hypothesized that children who participated in a four-week behavior modification program in which the mothers were the change agents would show improvement in eating habits; whereas the children in the control group would show no change. All the cases in the experimental group showed improvement above 90%, whereas no change was observed in the control group. nle results of the study indicate that the mother's worries and attitudes play the most important role in initiating feeding difficulties, and changing her attitude and educating her in how to deal with the problem leads to improvement in the child.
Keywords: Food habits -- Psychological aspects.; Nutrition disorders in children.; Children -- Nutrition.